OBTAINING AND EFFICIENCY OF STEEL CASTING IN LOCAL CONDITIONS IN MECHANICAL ENGINEERING (Academicia Globe: Inderscience Research, 2021)
The selection is based on the way they are used, taking into account the variety of casting methods. Of course, as we continue our scientific work, we will focus more on the injection molding method.